Introducing a novel chemical method of treatment for dye removal: Removal of Maxillon Blue and Direct Yellow from aqueous solution - Aseel M Aljeboree (University of Guilan, 2021)
Many industrial and chemical dyes are used in many industrial processes, a variety of different uses. Among the most important of these industries, fabric dyeing, many textiles, papermaking, printing and leather processing, and most food products, and other industries, use industrial dyes, and the waste emitted from these dyes in most industries in which most of the polluted waste resulting from these remnants is produced factories. Therefore, the best methods were adopted to treat and dispose of these dyes in order to preserve the aquatic environment .In the current study, the adsorption characteristics of two dyes, Maxillon blue (GRL) and Direct yellow (DY12), from an aqueous solution were evaluated. The effect of several factors, for example, initial concentration, pH solution, temperature, adsorbent mass, and equilibrium time, have been study. The adsorption capacity and percentage of color removed upraised by elevating contact time and surface area, also elevated by the upraised temperature solution for GRL and DY12, and also the adsorption efficiency decreased by the raised adsorbent dosage. The optimum equilibrium for contact time to be completed is found to be (60 min) 1 hour. It is essentially due to the saturation of the active site that does not let further adsorption to take place. The adsorption was proved through utilizing (FT-IR) and (F.E-SEM) analysis. In addition, TGA appears that the NTADCIP/P (AA-co-AM) composite is stable in high temperatures. GRL adsorbent surfaces best adsorption found to be at pH = 10. In fact, adsorption was found to increase through the rise in solution pH.  However DY12 maximum dye adsorption was found to be at pH = 3.  The applicability of isotherms adsorption to study the adsorption behavior has to been analyzed via isotherm models Freundlech and Langmuir were utilized to illustrate the experimental model and isotherm's constants. It was found the Freundlech model gives the best fits when compare with Langmuer isotherm for two dyes.